PALMPRINT RECOGNITION SYSTEM BASED ON GRAY LEVEL CO-OCCURRENCE MATRIX - Caliskan, Abidin; Ergen, Burhan (Ieee, 2014)
A biometric system provides automatic identification of individuals based on a unique feature or characteristic of the individuals. Palmprint biometric system has an important place among biometric identification systems because of its advantages. In this study, Gray Level Co-Occurence Matrix based palmprint recognition system which provides successful results for tissue type of image identifying has been proposed. Firstly, image coordinate system has been defined to facilitate image alignment for feature extraction. Then, region of interest is cropped from the palmprint images. The properties of the interested region have been determined using the developed system and it has been given to the classifier for recognition.
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: Biometric system; Palmprint recognition; Gray Level Co-occurrence Matrix